有序异质论视角下的“普通行话” - Chen, Jingyu (БНТУ, 2021)
With the trend of peripheral language moving towards the central language at the end of the 20th century, more and more jargons have entered the vocabulary system of standard language, resulting in a new lexemic stratum - common jargon. It’s not only the result of the blurring line between standard and non-standard language, but also a proof of the variability of language system. This article used the Ordered Heterogeneity Theory on Language Variation to explain common jargon.